2009
DOI: 10.1143/apex.2.021102
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of InGaZnO4Thin Film Transistors Characteristics Utilizing Excimer Laser Annealing

Abstract: This paper describes a method for utilizing an excimer laser to improve the characteristics of InGaZnO 4 (IGZO) thin-film transistors (TFTs). IGZO-TFTs fabricated at room temperature are irradiated with an excimer laser to raise the temperature of the IGZO films for only a very short time, some tens of ns. The ON current of an irradiated IGZO-TFT is more than one order of magnitude higher than that of an unirradiated TFT. This method is promising for achieving high performance IGZO-TFTs on plastic substrates b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 10 publications
4
33
0
Order By: Relevance
“…A drastic variation from low conductivity to high conductivity occurs at a critical laser energy density ͑10.7 mJ/cm 2 ͒ or at a critical UV irradiation time. The influence of laser energy density on IGZO conductivity was also reported by Nakata et al 5 when they used a XeCl excimer laser to treat an IGZO film. In their article, increasing laser energy density also significantly increases IGZO conductivity, and a critical laser energy density such as 90 mJ/cm 2 is observed.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…A drastic variation from low conductivity to high conductivity occurs at a critical laser energy density ͑10.7 mJ/cm 2 ͒ or at a critical UV irradiation time. The influence of laser energy density on IGZO conductivity was also reported by Nakata et al 5 when they used a XeCl excimer laser to treat an IGZO film. In their article, increasing laser energy density also significantly increases IGZO conductivity, and a critical laser energy density such as 90 mJ/cm 2 is observed.…”
Section: Resultssupporting
confidence: 67%
“…5 Although the authors did not mention stability issues, they successfully demonstrated the feasibility of using ELA on IGZO TFTs. In our study, two low temperature annealing methods are proposed to effectively solve the stability problem.…”
mentioning
confidence: 99%
“…In this study, we focused on an IZO TFT with a higher field-effect mobility than an a-IGZO TFT. We assumed that an ELA process crystallizes IZO with nanograins easily since this material has a lower crystallization temperature than a-IGZO 12,13 and that an IZO film composed of nanograins has better characteristics than a noncrystallized IZO TFT since carrier scattering is suppressed in the disordered film. We considered it is necessary to use a laser with a wavelength shorter than 400 nm, for the laser to be absorbed by the IZO film since IZO has a wide band gap (higher than 3 eV).…”
mentioning
confidence: 99%
“…In general, furnace annealing above 300 • C is effective for obtaining good transfer characteristics and stable IGZO-TFTs [9]- [11], but processing temperatures above 150 • C are not compatible with most flexible polymer substrates. To address the low temperature integration issue, excimer laser annealing (ELA) has been explored [12], [13]. However, the small laser beam size is a major limitation to meet the high throughput and low-cost demands of large area roll-to-roll manufacturing.…”
Section: Introductionmentioning
confidence: 99%